The Mechanisms Underlying Cocaine-Induced Overexpression of Basic Fibroblast Growth Factor (bFGF, FGF2), an Effect Reversed By Extinction - (:unkn) unknown (My University, 2016)
Drug addiction is characterized by compulsive drug use and chronic relapse despite negative consequences. Drug-induced structural and functional changes in the brain are thought to underlie these characteristics. One mechanism that may mediate these characteristics are growth factors, such as basic fibroblast growth factor (bFGF or FGF2), as they are necessary for cellular growth, survival, differentiation, and have roles in memory, mood, and anxiety disorders. bFGF mRNA and protein expression is increased following stimulant administration and is necessary for stimulant-induced changes in dendrites and behavioral sensitization. Moreover, addiction is maintained by cues associated with the drug, as they can can evoke craving and promote relapse. Therefore, reducing cue reactivity, such as with extinction, could reduce relapse rates. Inhibiting bFGF in the infralimbic medial prefrontal cortex (IL-mPFC), following self-administration, facilitates extinction. Extinction of drug seeking can reduce bFGF expression in IL-mPFC, nucleus accumbens (NAc), and dorsal hippocampus (dHipp), indicating that bFGF may mediate drug-associated learning. However, the circuitry and mechanisms underlying extinction and the role of bFGF is unknown. Therefore, the current experiments investigated if drug-induced plasticity was altered by extinction and if bFGF had a role, in brain regions associated with learning or addiction (i.e., IL-mPFC, NAc, and dHipp). We found that cocaine self-administration induced changes in plasticity-related protein expression, such as ARC and pGSK3beta, in each brain region, and extinction could ameliorate some of that plasticity. Moreover, we found that neutralizing bFGF in NAc prior to four 30-min extinction sessions disrupted initial extinction retention. However, if bFGF was neutralized without four 30-min extinction sessions, subsequent extinction was enhanced. In dHipp, neutralizing bFGF, with or without four 30-min extinction sessions, facilitated subsequent extinction over days. Overall, these results suggest that blocking the biological function of bFGF in a number of reward- and learning-related brain regions can facilitate subsequent extinction. Understanding the neuronal mechanisms by which bFGF regulates extinction at systems and molecular levels will allow for development of new pharmacotherapeutics to enhance extinction-based therapies for addiction.
Keywords: Addiction Treatment; Drug-Associated Learning; Memory; Plasticity; Self-Administration; Withdrawal